Using action research as process for sustaining knowledge production: A case study of a higher education qualification for academics - du Toit, Pieter H (South African Journal of Higher Education, 2016)
The study reported in this paper focuses on the idea that I, as academic specialising in higher education, monitor and gather data about my practice, alongside colleagues enrolled for a formal professional qualification in higher education, with a view to sustaining scholarly and professional development. I do this to improve my practice in an innovative and accountable way, which includes constructing new meaning and contributing to the production of knowledge in the fields of facilitating learning in higher education and academic staff development. The illustrative case study is the Postgraduate Certificate in Higher Education (PGCHE). Cultivating scholarly higher education practitioners is viewed as an important aim of the programme. The focus is on constructing one’s own understanding of one’s higher education practice in a scholarly way. Learning theories, including self-regulated professional learning and constructivist learning, as is to be found in the principles of action research, form an integral theoretical underpinning for scholarly development. Action research is used as a means of sustained professional learning for all participants. My study investigates how professional learning can be encouraged and sustained through the development and assessment of professional development portfolios. The portfolios came to represent the living theories (McNiff 2002) of practice of all participants, substantiating educational values and claims of improved practice. The process of compiling the portfolios is based on the principles of action research. This process is in stark contrast with the notion that a portfolio is ‘a file of evidence’. They rather represent evidence of new knowledge produced/constructed. A mix of research methods is used to obtain data – gathered, by means of a learning style questionnaire, text analysis and photo evidence. Other methods such as observation, student feedback questionnaires and interviews are not reported. Keywords: Whole brain learning, constructivist learning, action research, professional portfolio, learning styles